Determinan Kepatuhan Pasien Tuberkulosis Paru Dalam Menjalani Pengobatan di UPT. Puskesmas Simalingkar Tahun 2024 - Barus , Nanda Isabel; Manurung, Kesaktian; Hutajulu , Johansen; Wandra , Toni; Girsang , Vierto Irennius (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Pulmonary tuberculosis (TB) is a chronic infectious disease that remains a major global and national public health problem, with Indonesia ranking second among countries with the highest TB burden worldwide. Non-adherence to treatment is one of the main barriers to successful TB control, as it may lead to treatment failure, drug resistance, and increased morbidity and mortality. At the Simalingkar Community Health Center (UPT Puskesmas Simalingkar), the specific factors determining treatment adherence among pulmonary TB patients have not been extensively studied. Objective: This study aimed to analyze the determinants of treatment adherence among pulmonary tuberculosis patients at the Simalingkar Community Health Center in 2024. Methods: This study employed an analytical cross-sectional design. The study population consisted of all pulmonary TB patients undergoing treatment at the Simalingkar Community Health Center, with a total sample of 90 respondents selected using a total sampling technique. Data were collected through questionnaires and medical records, and analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses, with a significance level of p < 0.05. Results: A total of 77.8% of patients were adherent to treatment. Bivariate analysis showed significant associations between education (p < 0.001), employment status (p = 0.004), knowledge (p = 0.006), and health care services (p = 0.011) with treatment adherence. Age, sex, and family support were not significantly associated with adherence. Multivariate analysis indicated that the most dominant factor associated with treatment adherence was educational level (OR = 9.004; 95% CI: 2.58–31.49), followed by employment status (OR = 5.59; 95% CI: 1.48–21.12), and health care service support (OR = 3.99; 95% CI: 1.09–14.56). Conclusion: The significant determinants of treatment adherence among pulmonary TB patients at the Simalingkar Community Health Center were educational level, employment status, and health care service support, with education being the most dominant factor. It is recommended that TB control programs place greater emphasis on interventions aimed at improving health literacy, socio-economic support, and the quality and accessibility of health care services to enhance treatment adherence.